Comparison of Magnesium Sulphate Loading Dose with & without Maintenance Regimen for Management of Patients Presenting with Eclampsia, Randomized Control Trial - Fouzia Rahat, Safdar Iqbal, Sadia Yahya, Ayesha Naz, Abida Khanam, Nuzhat Parveen Khawaja, Arslan Saleem Chughtai (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the frequency of recurrence of convulsions with Magnesium Sulphate loading dose versus loading dose plus maintenance regimen for management of patients presenting with eclampsia. Methods: In this Randomized Controlled Trial, 240 pregnant female admitted in department of Obstetrics & Gynaecology, LGH, Lahore. Half In group A, females were given MgSO4 in a single bolus dose i.e. 4 grams intravenously diluted in 100ml normal saline over 20 minutes and 10grams intramuscularly, while in group B, females were given complete standard regime according to the Pritchard i.e. 14 grams loading dose followed by 5gm intramuscularly every 4 hours on alternate buttock for 24 hours after the last episode of convulsion or delivery of the fetus whichever comes later. Results: In this study recurrence of convulsion was significantly higher in patients who were given MgSO4 loading dose as compared to patients who were given MgSO4 loading + maintenance regimen i.e. Group-A: 15.8% vs. Group-B: 5.8%, (p-value 0.013). The frequency of recurrence of convulsion was significantly higher in women who were given loading dose alone as that of women who were given MgSO4 loading + maintenance regimen but Age, gestational age and parity status of women although did not show any significant association.. Conclusion: Loading dose plus maintenance regimen had low frequency of recurrence convulsion when compared with loading dose of MgSO4 only.